Incidence of Sacroiliac Joint Dysfunction as a Cause of Low Backache: An Under-Appreciated Pain Generator (Medical Forum Monthly, 2023)
Objective: To determine the prevalence of low back pain in a pain clinic of a tertiary care Hospital and to assess its association with sacroiliac joint dysfunction.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Holy Family Hospital Rawalpindi from October 2021 to May 2023.Materials and Methods: This study included 2116 individuals of both genders who visited Holy Family Hospital's specialized pain clinic complaining of pain. The presenting complaints, diagnosis, age, and gender were noted to characterize the pattern of diseases among patients attending the specialized pain clinic.Results: Patients selected for this study were 37.7% male and 62.3% female, averaging 44.25 ± 7.04 years. Lower back pain (30.1%) was the most common presenting complaint while paraspinal muscle spasms & trigger points (54%), and sacroiliac joint dysfunction (26.6%) were the most common diagnoses made for the patients presented with lower back pain. Disease-related pain was significantly correlated with gender.Conclusion: The findings of our study will be helpful in directing clinicians' attention away from the intervertebral disc and toward the sacroiliac joint to prevent needless and invasive therapies.